2023
DOI: 10.1039/d2ta09702h
|View full text |Cite
|
Sign up to set email alerts
|

Elemental doping inhibits surface-state-mediated charge carrier trapping for promoting photocatalytic selective oxidation

Abstract: Surface-state-mediated trapping process, a dominant consumption pathway of photoinduced charge carrier, sometimes plays a detrimental effect on gaining high-efficiency photocatalytic solar energy utilization. Herein, taking Bi2O2CO3 as a typical prototype,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This interaction enhances the stability of the doped structure. 32,33 On the other hand, the intrinsic charge transfer behaviour of the basal plane can be modified by introducing nonmetallic dopants with different valence electrons into the basal plane or by exploiting the electronegativity difference between the doped nonmetallic atoms and the basal plane atoms, which can ultimately enhance the photocatalytic HER performance. [34][35][36] Recently, Cui and colleagues have identified that BiOCl co-doped with S and Mo exhibits enhanced photocatalytic activity for pollutant degradation.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction enhances the stability of the doped structure. 32,33 On the other hand, the intrinsic charge transfer behaviour of the basal plane can be modified by introducing nonmetallic dopants with different valence electrons into the basal plane or by exploiting the electronegativity difference between the doped nonmetallic atoms and the basal plane atoms, which can ultimately enhance the photocatalytic HER performance. [34][35][36] Recently, Cui and colleagues have identified that BiOCl co-doped with S and Mo exhibits enhanced photocatalytic activity for pollutant degradation.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 To ameliorate this, various strategies have been employed, such as cocatalyst modification, element doping, and heterojunction construction. [19][20][21][22] Noble metals with high function and low Fermi levels, such as Pt, 23 Ag, 24 and Au, 25 are common H 2 production cocatalysts, and can provide active sites for electron transport and reduce the H 2 production overpotential. Efficient H 2 production is conducive to promoting the oxidation of BA; for example, Ruberu et al demonstrated that loading Pt on CdS nanorods significantly promoted the activity of photocatalytic BAD synthesis, which was ascribed to the fact that the Pt cocatalyst accelerated the reaction kinetics of H 2 production.…”
Section: Introductionmentioning
confidence: 99%